Problem Based Learning-Oriented E-Module to Innovate Learning Activities in High School - Aladin; Asrowi; Santosa, Eka Budhi (LPPM Undiksha, 2024)
In the continuously evolving digital era, digital teaching materials in the form of e-modules have emerged as a promising alternative to enhance the effectiveness of learning, particularly in high schools. Furthermore, e-modules as instructional materials can be integrated with various innovative approaches and models of learning, such as problem-based learning. Therefore, this research aims to develop an innovative problem-based e-module for computer science education that is deemed suitable as a learning medium. The research method employed is research and development, adopting the ADDIE model. The research subjects include media experts, subject matter experts, instructional design experts, and students. Data collection is conducted through a media feasibility questionnaire, The data collection instrument uses a feasibility questionnaire for each expert, practitioner and student. As for data analysis was using descriptive percentages. The research findings indicate that the developed e-module received a